1998
DOI: 10.1097/00006223-199803000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Research Utilization by Undergraduate Students

Abstract: In our experience as nurse educators, baccalaureate students, after completing an introductory research course, are not prepared to critique research studies skillfully and determine their potential use in professional practice. Also, staff nurses need help determining the appropriateness of implementing research findings into clinical practice. To remedy this situation, a research utilization component was successfully incorporated into a senior-level clinical course. This approach has implications for improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Research courses are now an accepted part of nursing curricula. Radjenovic and Chally (1998) indicated that 90% of baccalaureate programs accredited by the NLN had a formal research course. The goals of teaching research are to foster the development of cognitive and professional skills, with emphasis on critical thinking and analysis and utilisation of research findings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research courses are now an accepted part of nursing curricula. Radjenovic and Chally (1998) indicated that 90% of baccalaureate programs accredited by the NLN had a formal research course. The goals of teaching research are to foster the development of cognitive and professional skills, with emphasis on critical thinking and analysis and utilisation of research findings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[ 1 ] Nurses claimed that they cannot assess the quality or accuracy of the findings and because of that, employment of the findings was questionable for them. [ 11 14 15 ] Also, newly graduated nurses needed more time to learn and adapt to a professional environment before they could implement the findings of research in their nursing practice. [ 16 ] Moreover, research utilization was influenced by personal and professional characteristics of nurses.…”
Section: Introductionmentioning
confidence: 99%
“…The faculty in baccalaureate nursing programs must incorporate nursing research throughout the curriculum. A single course on research process is no assurance that even the best and brightest students will be prepared to perform the investigative functions of a nurse with a baccalaureate degree in nursing (15). Previous research studies recommend nursing research courses and concepts be introduced into the nursing curriculum as early as possible, since research courses and concepts improve nursing students' positive attitudes toward nursing research (16,17).…”
Section: Introductionmentioning
confidence: 99%